Artificial Intelligence in Digital Art: A Comparative Analysis on Impacts to Artists - Cajulis, Richard Christopher Jude; Tuazon, Jakob Adrian; Cabauatan, Ronaldo R. (International Journal of Arts, Recreation and Sports, 2025)
Purpose: This study explores the evolving relationship between artists and AI tools in the digital art world. AI's ability to mimic artistic styles and generate new ideas challenges traditional notions of art creation. While AI offers potential benefits like workload reduction and creative inspiration, concerns remain about its impact on artist income and creative processes. Methodology: The research investigates artist satisfaction with AI-generated works, the impact on workflow efficiency, and the potential for income changes. It aims to understand how artists perceive these tools and how AI is affecting their creative ecosystem. Findings: The study anticipates that traditional and blended approaches will hold higher value due to the unique skills and time invested. Findings revealed a three-tiered artist landscape: 1) traditional artists, 2) artists who blend AI and traditional methods, and 3) artists solely using AI tools. The research sheds light on the complex interplay between technological innovation, creative expression, and financial viability within the digital art domain. Unique Contribution to Theory, Policy and Practice: The study employs economic theory of production to analyze the impact of AI on artistic production. In the context revenue, satisfaction, and workload, artists in Manila, Philippines are willing to use AI tools in order to increase their revenue, have a felicitous satisfaction, and reduce their workload that align with the client’s needs. While AI tools can be valuable assistants, the human element remains central to the creative process.